Conformational Propensities of a DNA Hairpin with a Stem Sequence from the c-MYC Promoter - Arees Garabet; Iztok Prislan; Nataša Poklar Ulrih; James W. Wells; Tigran V. Chalikian (Biomolecules)
G-quadruplexes and i-motifs are four-stranded non-canonical structures of DNA. They exist in the cell, where they are implicated in the conformational regulation of cellular events, such as transcription, translation, DNA replication, telomere homeostasis, and genomic instability. Formation of the G-quadruplex and i-motif conformations in the genome is controlled by their competition with the pre-existing duplex. The fate of that competition depends upon the relative stabilities of the competing conformations, leading ultimately to a distribution of double helical, tetrahelical, and coiled conformations that coexist in dynamic equilibrium with each other. We previously developed a CD spectroscopy-based procedure to characterize the distribution of conformations adopted by equimolar mixtures of complementary G- and C-rich DNA strands from the promoter regions of the c-MYC, VEGF, and Bcl-2 oncogenes. In those bimolecular systems, duplex-to-tetraplex and duplex-to-coil transitions are accompanied by strand separation and an associated entropic cost. This situation is distinct from the pseudo-monomolecular nature of conformational transformations within the genome, where strand separation does not occur. To mimic better the situation in the genome, we here extend our studies to a monomolecular DNA construct—a hairpin—in which complementary G- and C-rich strands featuring sequences from the promoter region of the c-MYC oncogene are linked by a dT11 loop. We used our CD-based procedure to quantify the distribution of conformational states sampled by the hairpin at pH 5.0 and 7.0 as a function of temperature and the concentration of KCl. The data were analyzed according to a thermodynamic model based on equilibria between the different conformational states to evaluate the thermodynamic properties of the duplex-to-coil, G-quadruplex-to-coil, and i-motif-to-coil transitions of the hairpin. The results have implications for the modulation of such transitions as a means of therapeutic intervention.